PENGARUH PIJAT HAMIL TERHADAP PERUBAHAN KUALITAS TIDUR IBU HAMIL TRIMESTER TIGA - Dian Anggraini, Rista; Hidayah, Ardiyanti (PRIMA WIYATA HEALTH, 2022)
Pregnancy have an impact on the quality of sleep for pregnant women, short gestational age or premature birth and are detrimental to the development of safar in the fetus. Pregnant massage can facilitate blood circulation, make the body relax, muscle tension in certain parts can be reduced (Aprillia, 2010), reduce cortisol hormone to reduce stress, neropineprin to reduce gold, serotine to reduce pain in the back and legs, low fetal activity , so that the quality of sleep for pregnant women increases, and the premature level in infants is low (field et al, 2004). Research design: this is a Quasi- experimental study with pre test and post test approaches. Results of the analysis: based on the Mann Whitney test results, there was no significant difference (v-palue = 0.104) average sleep quality in pregnant women in the third trimester before and after pregnancy without pregnancy. There is a significant difference (v-palue = 0.001) average sleep quality of third trimester pregnant women before and after pregnancy massage. There is a significant difference in mean difference in sleep quality in third trimester pregnant women in the group with pregnant or not massage (v-palue = 0.049). Conclusion: There is an effect of pregnant massage on changes in sleep quality of third trimester pregnant women